2022
DOI: 10.3389/fcell.2021.782529
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Characterization of Tumor Purity and Its Clinical Implications in Gastric Cancer

Abstract: Solid tumour tissues are composed of tumour and non-tumour cells, such as stromal cells and immune cells. These non-tumour cells constitute an essential part of the tumour microenvironment (TME), which decrease the tumour purity and play an important role in carcinogenesis, malignancy progression, treatment resistance and prognostic assessment. However, the implications of various purity levels in gastric cancer (GC) remain largely unknown. In the present study, we used an in-silico approach to infer the tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 57 publications
3
14
0
Order By: Relevance
“…Notably, our findings indicated that patients of C1 subtype typically exhibit higher tumor purity. As previous reports, a higher tumor purity generally reveals a better prognosis in GC and more likely to benefit from adjuvant chemotherapy [ 43 , 44 ], which not only validated the better survival of C1 subtype but also suggested that C1 patients might benefit more from neoadjuvant chemotherapy.…”
Section: Discussionsupporting
confidence: 77%
“…Notably, our findings indicated that patients of C1 subtype typically exhibit higher tumor purity. As previous reports, a higher tumor purity generally reveals a better prognosis in GC and more likely to benefit from adjuvant chemotherapy [ 43 , 44 ], which not only validated the better survival of C1 subtype but also suggested that C1 patients might benefit more from neoadjuvant chemotherapy.…”
Section: Discussionsupporting
confidence: 77%
“…Notably, we found that the tumor purity of CM patients with high-risk scores was higher than that of patients with low-risk scores, suggesting a higher proportion of tumor cells in the tumor tissue. Generally, a high tumor purity implies a shorter survival probability and is more likely to be diagnosed as malignant (Lou et al, 2021). In this study, we found that better overall survival was correlated with lower tumor purity and higher immune score, indicating that patients with high-risk scores have worse survival status.…”
Section: Discussionmentioning
confidence: 52%
“…The low infiltration of CD8 T cells and the high infiltration of memory-activated CD4 T cells in type B GC cancer may increase the efficacy of immune checkpoint inhibitor therapy in GC patients. Decreased tumor purity also plays a vital role in the malignant progression of GC, treatment resistance, and prognostic assessment (38). These differences in the infiltration of immune cells may be related to the differences in the prognosis and clinical pathological stages of the patients with different subtypes.…”
Section: Discussionmentioning
confidence: 99%